Types of fraud in meat and meat products: a review - Espinoza, T. (2015)
Prevent fraud has become great interest in the recent years by state organizations and companies because it affects the food control. The globalization, increased imports and exports and free trade agreements have led to greater sharing and access to food worldwide; along with it, the problems associated with fraud such as adulteration, substitution, intentionality, and counterfeiting have been increased. Therefore, there are various tasks associated with food fraud, which in most reviews published only new identification techniques have been discussed. However, a discussion about the types of fraud and its impact on society, bioterrorism and religion, has been little commented. This review focuses primarily on describing the types of fraud that has as objective to obtain economic benefit or cause terrorism. Also, latest techniques available for detecting meat adulteration are mentioned.